(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
Theoretical analysis and generalization of teaching experience made it possible to figure out that the problem of professional training future teachers of physical education is considered in the context of updating of educational process in high school, forming needs professional self-development specialist in the field of sports and continuous improvement of pedagogical skills. The results of the pedagogical experiment show that the value-meaningful and activity-reflective orientation of the teacher’s self-development ensures his professional growth, which is reflected in specific indicators: the professional values of self-development are approved; the teacher’s need for his own professional development and self-development is realized; methods of self-discovery and self-analysis of pedagogical experience are mastered; the ability to reflect develops, which is a necessary attribute of a professional teacher; the readiness and ability for pedagogical creativity develops. On the basis of the conducted pedagogical experiment, taking into account interviews (questionnaires, surveys) of teachers of higher education institutions and school teachers, it is advisable to recommend the introduction of a special course of professional self-development of physical education teachers in pedagogical higher education institutions, a plan for self-education of teachers, taking into account general recommendations for increasing motivation for their own professional and pedagogical self-development For students, teachers and researchers working in sphere of physical education.